Masalah dan Penyelesaian untuk Amalan Perlantikan Subkontraktor dalam Pengurusan Pembinaan - Muhammad Sukri, Ahmad Haikal; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2022)
The construction industry is getting better day by day. Following the launch of the New Economic Policy (NEP) by the third Prime Minister Tun Abdul Razak Dato ’Hussein in 1976, this greatly helped’ Bumiputera ’contractors in procuring government contracts. This problem will involve provision for subcontracted projects, which will pose problems with time, quality, and cost. This study was conducted to identify issues that arose in the conduct of subcontractors and to find a way out for these problems. This study takes a quantitative approach, using sampling in subcontract training. Thematic data analysis was used to analyze the data for this study, with the scope of this study focusing on Johor Bahru. Selected contractors range from grade 6 to grade 1 and are involved in subcontracting. Finally, the construction industry should be aware of the existence of subcontract forms issued by authorities such as CIDB, ​​which should be used in subcontracting practices to address such issues.